2019
DOI: 10.1186/s13014-019-1400-3
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive radiotherapy for head and neck cancer reduces the requirement for rescans during treatment due to spinal cord dose

Abstract: BackgroundPatients treated with radiotherapy for head and neck (H&N) cancer often experience anatomical changes. The potential compromises to Planning Target Volume (PTV) coverage or Organ at Risk (OAR) sparing has prompted the use of adaptive radiotherapy (ART) for these patients. However, implementation of ART is time and resource intensive. This study seeks to define a clinical trigger for H&N re-plans based on spinal cord safety using kV Cone-Beam Computed Tomography (CBCT) verification imaging, in order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 50 publications
(62 reference statements)
1
29
0
Order By: Relevance
“…ART has begun to play an increasingly prominent role in the treatment of HNC for 2 primary reasons: (1) significant tumor shrinkage, weight loss, and large anatomic deformations of OARs are often observed for HNC patients during RT, [22][23][24] and (2) treatment-related side effects from conventional RT can be particularly debilitating for patients with HNC and often persist for years after treatment. 25,26 Several studies have shown clinically significant reductions in doses to the parotid glands, [27][28][29] spinal cord, 29,30 and swallowing-related structures 31,32 with 1 or more offline plan adaptations during the course of RT. Because offline adaptive replanning is time and resource intensive, many studies have focused on identifying anatomic and dosimetric guidelines to determine when plan adaptation would be optimally effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ART has begun to play an increasingly prominent role in the treatment of HNC for 2 primary reasons: (1) significant tumor shrinkage, weight loss, and large anatomic deformations of OARs are often observed for HNC patients during RT, [22][23][24] and (2) treatment-related side effects from conventional RT can be particularly debilitating for patients with HNC and often persist for years after treatment. 25,26 Several studies have shown clinically significant reductions in doses to the parotid glands, [27][28][29] spinal cord, 29,30 and swallowing-related structures 31,32 with 1 or more offline plan adaptations during the course of RT. Because offline adaptive replanning is time and resource intensive, many studies have focused on identifying anatomic and dosimetric guidelines to determine when plan adaptation would be optimally effective.…”
Section: Discussionmentioning
confidence: 99%
“…Because offline adaptive replanning is time and resource intensive, many studies have focused on identifying anatomic and dosimetric guidelines to determine when plan adaptation would be optimally effective. 30,31,33 However, the clinical introduction of the 1.5T MR-linac has made daily ART for HNC a feasible clinical reality.…”
Section: Discussionmentioning
confidence: 99%
“…If the last generation of Linear accelerators like (MRI-Linac) or CBCT adaptive radiotherapy [36][37][38] is used, it implies a possible scenario where QC is without an irradiation of a real phantom, because image acquisition (MRI or CBCT), contouring, dose calculation and finally dose delivery should be done without change position of the patient. The MC as independent platform of QC of patient dosimetry could by the optimal solution since it has many advantages like most accurate dose calculations, saving linear accelerator time and performing QC of the machine by using log files as input MC dose calculations.…”
Section: Discussionmentioning
confidence: 99%
“…ART has begun to play an increasingly prominent role in the treatment of HNC for two primary reasons: 1) significant tumor shrinkage, weight loss, and large anatomical deformations of OARs are often observed for HNC patients during RT [16][17][18]; and 2) treatment-related side effects from conventional RT can be particularly debilitating for HNC and often persist for years after treatment [19,20]. Several studies have demonstrated clinically significant reductions in doses to the parotid glands [21][22][23], spinal cord [23,24], and swallowing-related structures [25,26] with one or more off-line plan adaptations over the course of radiotherapy. Because offline adaptive re-planning is time-and resource-intensive, many studies have focused on identifying anatomical and dosimetric guidelines to determine when plan adaptation would be optimally effective [24,25,27].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated clinically significant reductions in doses to the parotid glands [21][22][23], spinal cord [23,24], and swallowing-related structures [25,26] with one or more off-line plan adaptations over the course of radiotherapy. Because offline adaptive re-planning is time-and resource-intensive, many studies have focused on identifying anatomical and dosimetric guidelines to determine when plan adaptation would be optimally effective [24,25,27]. However, the clinical introduction of the 1.5T MR-linac has made daily ART for HNC a feasible clinical reality.…”
Section: Discussionmentioning
confidence: 99%